PELATIHAN PEMBUATAN PUPUK BOKASHI SEBAGAI MEDIA TANAM ORGANIK PADA LAHAN PEKARANGAN - Astar, Ismail; Suci, Ida Ayu; Suryani, Rini (Jurnal Abdi Insani, 2024)
The Ornamental Grass Waste Bank (BSRH) is an institution with a cooperative legal entity, the establishment of which is facilitated by the Pontianak City Government through the Pontianak City Environmental Service. Until now, BSRH has focused more on managing inorganic waste in handicraft materials, decorations, and souvenirs. Meanwhile, some organic wastes are processed into organic fertilizers. The obstacle faced by the BSRH is the non-optimal management of organic waste into fertilizer because of the lack of skilled personnel in processing waste into organic fertilizer.  This PKM activity aims to transfer knowledge about organic waste processing using effective decomposing microorganisms. The implementation method used in this activity consists of three stages: preparation, implementation and training, and monitoring and evaluation. Based on the results of the activities that were carried out, it was found that all BSRH members who participated in the training and practice of making bokashi from organic waste gained new understanding and knowledge in utilizing organic waste as bokashi fertilizer and interest in applying it in the future. From the questionnaire given, data showed that 80% of BSRH members had never participated in similar activities, while all BSRH members (100%) stated that the training activity on making bokashi fertilizer from organic waste was useful, providing new knowledge and interest in its application. This training and practice of making bokashi fertilizer can provide knowledge and skills for solving problems regarding organic waste in the surrounding environment into more useful materials.